Optical Tomography Sensor Configuration for Estimating the Turbidity Level of Water - Mohd Taufiq Mohd Khairi; Sallehuddin Ibrahim; Mohd Amri Md Yunus; Mohd Najmi Mohd Sulaiman; Mahdi Faramarzi (Institute of Advanced Engineering and Science, 2014)
This paper presents an investigation on an optical sensor configuration to estimate the turbidity level in a sample of water based on tomography technique. The optical sensors consist of infrared light - emitting diodes (LED) as transmitters and photodiodes as the receivers where the projections of the sensors are designed in fan beam mode. The promising results obtained from the analysis of light path detection demonstrated the accuracy of the proposed technique in estimating the turbidity level of water. The approach has potential to contribute and utilize for monitoring the quality level of water in water treatment industries.